Influence of technique variation training on technique variability in long distance running - Rein, R.; Simon, Ch. (International Journal of Computer Science in Sport, 2002)
The application of complex systems theories in the field of human coordination had been mainly focused on simple movements. In contrast, the present study tried to apply the derived principles on a complex movement: long distance running. In detail the influence of technique variation training on technique variability in long distance running was examined. 16 competitive middle and long distance runners (aged, 21.7 ± 7.4 years) divided into an experimental (n=8) and a control group (n=8) took part in this study. During the investigation period of three months both groups continued their standard endurance training while the experimental group carried out additional technique variation training. Before and after the investigation period both groups were filmed during a stepwise test with two digital high speed cameras. The variability of the running technique was measured by the means of an analysis of the foot-, knee-, hip- and elbow-angle kinetics. The technique variation training was designed considering principles derived from complex systems theory. Running technique was identified as a local attractor while movement variations played the role of fluctuations. The induced fluctuations should provide a mechanism that destabilises local attractors (in this case the initial running pattern) and enabled the system to discover new stable movement modes under the paradigm of self-organization. To support the process of final stabilization the amplitudes of variation were systematically reduced during the investigation period. To determine the individual variability of the running technique a fast Fourier transformation and a comparison of the complex Fourier coefficients of the angle kinetics were carried out. A repeated measure ANOVA showed a significant difference between the two test situations for the experimental group. The technique variability of the experimental group decreased significantly while the control group showed no significant changes. The results show that additional technique variation training can change the stability properties of technique in long distance running. Thus, the consideration of complex system theory in the field of human coordination can lead to direct sport-practical applications.